Taxonomic revision of the genus Tupirinna Bonaldo, 2000 (Araneae: Corinnidae: Corinninae) - Xavier, Cláudia; Bonaldo, Alexandre B. (Zootaxa, 2021)
The genus Tupirinna Bonaldo, 2000 is revised, including 20 species. New records of T. rosae Bonaldo, 2000 from Pará, Brazil are given. Tupirinna albofasciata (Mello-Leitão, 1943) is redescribed based on the female lectotype, here designated. The following 17 new species are described, diagnosed, and illustrated: T. platnicki sp. nov. (♂ and ♀ from Pará, Brazil); T. zebra sp. nov. (♂ and ♀ from Amazonas and Mato Grosso, Brazil); T. caraca sp. nov. (♂ and ♀ from south and southeast Brazil); T. urucu sp. nov. (♂ from Amazonas, Brazil); T. coari sp. nov. (♂ and ♀ from Amazonas, Brazil); T. lata sp. nov. (♂ and ♀ from the states of Bahia, Espiríto Santo, Minas Gerais, São Paulo and Santa Catarina, Brazil); T. regiae sp. nov. (♂ and ♀ from Amazonas and Pará, Brazil); T. mutum sp. nov. (♂ and ♀ from Pará and Mato Grosso, Brazil); T. cruzes sp. nov. (♂ and ♀ from Rio de Janeiro, São Paulo and Santa Catarina, Brazil); T. palmares sp. nov. (♂ and ♀ from northeast Brazil); T. una sp. nov. (♂ and ♀ from Bahia, Brazil); T. gigantea sp. nov. (♂ and ♀ from Vaupés, Colômbia and Peru); T. oba sp. nov. (♀ from Bahia, Brazil); T. goeldi sp. nov. (♀ from Pará, Brazil); T. ibiapaba sp. nov. (♂ and ♀ from Ceará, Brazil); T. luctuosa sp. nov. (♀ from Minas Gerais, Brazil) and T. araguaia sp. nov. (♂ and ♀ from Pará, Brazil). Additionally, two species groups are delimited based on genitalic morphology. Distribution maps and an identification key to the males and females of all known species of Tupirinna are also provided.